Plasma deposited high surface area‐activated carbon coatings: Theory combining particle generation, aggregation and deposition explains microstructure. Issue 8 (15th April 2022) - Tran, Clara T.; Raco, Michael; Casey, Louis M.; McKenzie, David R.
Abstract: High surface area carbon coatings are produced by plasma‐enhanced chemical vapour deposition using a high‐voltage dielectric barrier discharge under conditions where aggregates are formed in the plasma and the growing coating is subjected to plasma immersion ion implantation. We extend the Smoluchowski aggregation theory to include the continuous production of monomers to explain the observed microstructure of the coatings as a function of the pressure of deposition. The larger particles show evidence of the accretion of monomers on their surfaces with characteristic voids resulting from island growth. The coatings are subjected to plasma immersion ion implantation using high‐voltage pulses that create radicals for binding biomolecules. The increased surface area by the presence of the aggregated particles binds a significantly higher amount of protein than smooth coatings, making them potentially useful for electrodes, biosensing and drug delivery. Abstract : The aggregation of carbon materials in ionized gases is a fundamental process in the universe. Here, we study it in the laboratory by introducing acetylene into a dielectric barrier discharge and interpret the findings using a kinetic theory of aggregation that extends the Smoluchowski equation. Pulsed negative bias voltages create ion bombardment that produces mechanically strong, high surface area carbon films containing uniformly sized aggregates that bind biological molecules covalently.